(untitled) (Intelligere, 2018)
This research is composed of two units coordinated among themselves: the translation into Portuguese of excerpts from the book Experiments on the generation of insects, by Francesco Redi (1626-1698), preceded by an analysis of the author's positions on the animal generation. The translated excerpts and the analysis carried out show that Redi, in addition to recognizing that the appearance of larvae on food was due to sexual reproduction in the flies, considered the existence of an intermediate type of spontaneous generation that would occur inside plants and live animals, from a certain "soul" or "virtue". In addition to considerations on the work of translation, the article contextualizes the work of Francesco Redi, highlighting his role in the development of observations and experiments with living beings in the early stages of the modern sciences